2016
DOI: 10.47102/annals-acadmedsg.v45n10p451
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety and Depression in Patients with Atopic Dermatitis in a Southeast Asian Tertiary Dermatological Centre

Abstract: Introduction: This study aimed to assess the frequency of anxiety and depression in a cohort of adult patients with atopic dermatitis (AD) in a tertiary dermatological centre, using the Hospital Anxiety and Depression Scale (HADS). We looked for any correlation between anxiety and depression with skin disease severity. Materials and Methods: Patients with AD were recruited from the National Skin Centre, Singapore, from 2008 to 2009 for a prospective cross-sectional study. The scoring atopic dermatitis (SCORAD)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 20 publications
(20 reference statements)
1
8
0
Order By: Relevance
“…Adults with AD perform significantly worse at work and have fewer job opportunities compared with healthy adults . Atopic dermatitis has been associated with depression and anxiety . However, the evidence for an association between AD and suicidality is inconclusive.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adults with AD perform significantly worse at work and have fewer job opportunities compared with healthy adults . Atopic dermatitis has been associated with depression and anxiety . However, the evidence for an association between AD and suicidality is inconclusive.…”
Section: Introductionmentioning
confidence: 99%
“…7 Atopic dermatitis has been associated with depression and anxiety. [8][9][10] However, the evidence for an association between AD and suicidality is inconclusive.…”
mentioning
confidence: 99%
“…The detection rates of depression and anxiety symptom in caretakers were higher than the findings of other studies on parental depression and anxiety [9,16]. Both the detection rates of anxiety and depression symptoms in caretakers of children with AD were higher than those reported from children and adult AD themselves [7,[17][18][19][20], which may be related to the specific disease characteristics of AD and more intimate parent-child relationship in China [21]. It was reported that compared with looking after a child with chronic asthma, caring for a child with chronic atopic eczema was associated with greater parental sleep disturbances [22].…”
Section: Discussionmentioning
confidence: 75%
“…The prevalence of ADHD in patients with AD was reported by 10 studies 12,15,23,27,30,34,36,46,52,59 ; all were published between 2009 and 2021. Forty‐two studies reported the prevalence of depression with AD 8,12,13,15,17,23–54,56–60 and were published between 2004 and 2021. Twenty‐four studies reported the prevalence of anxiety in AD, 8,12,13,17,23,26,27,29,31,34–37,42,43,45–49,52,56,58,60 between 2012 and 2022.…”
Section: Resultsmentioning
confidence: 99%
“…Subsequently, 221 articles were subjected to full‐text review; 178 were removed because they lacked clear diagnostic criteria, the type of research was unclear, the irrelevance of the topic, lack of English language, missing data, no reporting of ethical content or informed consent, or duplication. Ultimately, 43 studies 8,12,13,15,17,23–60 were included in the meta‐analysis and all were published between 1998 and 2022. Among the retrieved articles, articles reporting AD with comorbid bipolar disorder, manic episodes, somatic symptoms, conduct disorder, alexithymia, obsessive‐compulsive diseases, attachment disorder, self‐reported memory impairment or autism spectrum disorder (ASD) ( n = 16, in total) were few; therefore, these were not included in the meta‐analysis.…”
Section: Resultsmentioning
confidence: 99%